Popular knowledge, Ethnomatematics and the use of Games for teaching Geometry (Research, Society and Development, 2021)
It is noticed that the students of the Brazilian public schools have difficulties in relation to the contents of mathematics in general, but this study deals specifically with the contents of geometry, with a focus on popular knowledge and the teaching and learning processes of the sciences , especially mathematics, as a source of differentiated attention in school pedagogical practices. The main scope is the apprehension of mathematical content, with a focus on geometry through emerging methodologies that support the use of games, and are based on popular knowledge, based on Ethnomathematics. The objective is to analyze the popular knowledge of ethnomathematics as a methodological alternative for understanding problems that exist in everyday school life, especially in elementary education, based on the reality of the student. The research was exploratory-descriptive, with a qualitative approach and the prevailing method of action research with empirical analysis. The locus of this study was a Municipal School of Early Childhood Education and Elementary Education in the city of Redenção, in the state of Ceará. The social subjects are students of the 8th year of elementary school. The methodological proposal was made through the use of educational resources (games) aimed at teaching Geometry. The results showed that the use of games brought meaning to the students, subjects of the research, and that, therefore, it is considered that the proposal combined with the game was effective for a more significant teaching of geometry.